The 'British' Carmen Sylva: recuperating a German-Romanian writer - Nixon, Laura Elizabeth (2014)
Carmen Sylva (1843-1916), a German princess and the first Queen of Romania, was a well-known royal figure and a prolific writer. Under this pseudonym, she published around fifty volumes in a wide variety of genres, including poetry, short stories and aphorisms. During her lifetime she was a regular feature in the British periodical press and visited Britain on numerous occasions. Widely reviewed – both celebrated and condemned for her ‘fatal fluency’ – Sylva’s work became marginalised after her death and has yet to be fully recovered. She has only recently received critical attention in her native Germany and has yet to be recuperated within British literary culture. This thesis will examine the reasons behind Sylva’s current obscurity as well as presenting the grounds for her reassessment. It will establish her connection to Britain, markers of which can still be found in its regional geography, as well as the scope of her literary presence in British periodicals. It will draw comparisons between Sylva and her contemporaries and will examine her contribution to fin-de-siècle British literary culture, analysing her short stories in order to detail her engagement with the ‘Woman Question’. This focus places Sylva at the centre of contemporary discussions and her often conflicting responses to such issues further our understanding of the complexity of nineteenth-century literary debates. In reassessing Sylva, this study will address broader notions surrounding the short story, popular fiction, and women’s writing, in order to question both current and contemporary attitudes to literature.